Sequências textuais narrativas e descritivas e suas marcas linguísticas: análise de dificuldades em redações de alunos do ensino médio - Costa , Douglas Geraldo da (2018)
Linked to the line of research Text speech and teaching: processes of reading and production of written and spoken text and the research group Theories and discursive and textual practices, this dissertation has the general objective to investigate difficulties for the production of narratives by high school students. The research is justified by the challenges that the textual production represents in high school and by its relation with the methodological precepts of Public Teaching, the mineiro in the case. Based on the theoretical basis of Adam (2011) regarding textual sequences, specifically the narrative and descriptive sequences, and considering the linguistic marks proper to these sequences, specifically nouns, adjectives and verbs. The research has as corpus of analysis a set of three essays produced by first year students. The analyses seek to identify the narrative sequences, describe the elements of the descriptive and analyze the linguistic resources used in the corpus. As a result of the analyzes, we identified above all difficulties in the use of verbal tenses, in orthography, paragraphs that present the concept of moral of the textual genre fable.